Accurate Determination of Boron Content in Halite by ICP-OES and ICP-MS - Zhang-kuang Peng; Zhi-na Liu (International Journal of Analytical Chemistry)
Boron element is widely distributed in different geologic bodies, and there are important geo-chemical applications in earth science. Halite is a common mineral found in sediment basin. However there is no good method to accurately measure the boron content in halite, which is mainly because Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES) and Inductively Coupled Plasma Mass Spectrometer (ICP-MS) are limited by the high salt matrix interference and the instrument detection limit. Thus enriching the boron element and removing the matrix interference are necessary before the measuring. In this paper, Amberlite IRA 743 boron-specific resin was applied to enrich the boron element and remove most of the high-salt matrix. The strong acid cation resin (Dowex 50 W×8, 200-400 mesh, USA) and weak-base anion resin (Ion Exchanger II, Germany) were mixed with equal volume, which could remove the foreign ions completely: meanwhile, the relative content of boron in the solution reached above 98%, and the recoveries ranged from 97.8% to 104%. 208.900 nm was chosen as the detection wavelength for ICP-OES, and the detection identification and quantification limits were 0.006 mg·L−1 and 0.02 mg·L−1, respectively. 11B was chosen as the measuring element for ICP-MS, and the detection identification and quantification limits were severally 0.036 mg·L−1 and 0.12 mg·L−1. The relative standard deviations ranged from 1.4% to 3.4% through six replicates under different salinities. Therefore, the process could be regarded as a feasible method to measure boron content in halite by ICP-OES and ICP-MS.